Project-Based Learning for Control of Hybrid Powertrains using a Simulation Model. Issue 17 (2022) - Steffen, Thomas; Fly, Ashley; Stobart, Richard
Abstract: This paper describes an activity and assessment in the module "Hybrid and Electric Vehicles" at Loughborough University, which aims to create engagement with the control of hybrid powertrains. A hybrid powertrain uses both an internal combustion engine and a battery powered electric motor, and the goal is to distribute the power demand across both in a way that achieves the "best of both worlds." It is a slightly unusual but highly popular control problem. The activity uses project-based learning, centred around an open-source simulation model and simulation library specifically created for teaching purposes. It provides a fast, abstract yet representative energy behaviour of the whole vehicle, and visualises key aspects of the powertrain and its energy balance. The assessment task is an open challenge, asking students to improve upon an existing basic control strategy. The marking process involves a computer-based assessment for vehicle economy, drivability, and emissions. This gives learners the opportunity to pursue a practical hands-on exercise, and to demonstrate a realistic engineering approach of their choosing.